2003
DOI: 10.1002/chir.10212
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in the oxidation of bufuralol, a chiral substrate, by human cytochrome P450s

Abstract: Bufuralol (BF), a nonselective beta-adrenoceptor blocking agent, has a chiral center in its molecule, yielding the enantiomers 1'R-BF and 1'S-BF. beta-Adrenoceptor blocking potency is much higher in 1'S-BF than in 1'R-BF. One of the metabolic pathways of BF is 1"-hydroxylation of an ethyl group attached at the aromatic 7-position forming a carbinol metabolite (1"-hydroxybufuralol, 1"-OH-BF), and further oxidation (or dehydrogenation) produces a ketone metabolite (1-oxobufuralol, 1"-Oxo-BF). Both 1"-OH-BF and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…(Ï©/ÏȘ)-Bufuralol is a nonselective ␀-adrenoceptor blocking agent; its major metabolic pathways in humans are oxidation and glucuronidation [16,17], and our recent study showed that there are seven major metabolic pathways in vitro [6]. Predictive multiple reaction monitoring (MRM) is the most sensitive approach in metabolite identification [18,19].…”
Section: Metabolite Identification and Validation In Hihsmentioning
confidence: 99%
“…(Ï©/ÏȘ)-Bufuralol is a nonselective ␀-adrenoceptor blocking agent; its major metabolic pathways in humans are oxidation and glucuronidation [16,17], and our recent study showed that there are seven major metabolic pathways in vitro [6]. Predictive multiple reaction monitoring (MRM) is the most sensitive approach in metabolite identification [18,19].…”
Section: Metabolite Identification and Validation In Hihsmentioning
confidence: 99%
“…(R)-Bufuralol was selected rather than racemic bufuralol because CYP2D6 displays substrate enantioselectivity for (R)-bufuralol over (S)-bufuralol (Dayer et al, 1987;Narimatsu et al, 2003;Masuda et al, 2005). CYP2D6 is responsible for 95% of racemic bufuralol 1Ј-hydroxylation clearance, whereas CYP2C19 is responsible for 5% and CYP1A2 has a small contribution (Ïœ1%) (Mankowski, 1999).…”
Section: Mao Et Almentioning
confidence: 99%
“…Moreover, different stereoisomers of a ligand may inhibit isoenzymes in different ways, which in turn may lead to varying pharmacokinetic and drug-drug interactions characteristics of the two stereoisomers [37]. Methylenedioxy-alkylamphetamine (MDMA, also known as XTC), for instance is a known chiral substrate for CYP2D6 and also are the chiral analogs methylenedioxy-ethylamphetamine (MDEA) and methylenedioxy-amphetamine (MDA), which are high affinity CYP2D6 substrates [38].…”
Section: On-line Coupling Of Chiral Hplc To the Cyp2d6 Ead Systemmentioning
confidence: 99%